Dye-sensitized solar cells based on nanocrystalline TiO2 films surface treated with Al3+ ions: Photovoltage and electron transport studies - Alarcón, Hugo (2006)
Nanocrystalline TiO2 films, surface modified with Al3+, were manufactured by depositing a TiO2 suspension containing small amounts of aluminum nitrate or aluminum chloride onto conducting glass substrates, followed by drying, compression, and finally heating to 530 °C. Electrodes prepared with TiO2 nanoparticles coated with less than 0.3 wt % aluminum oxide with respect to TiO2 improved the efficiency of the dye sensitized solar cell. This amount corresponds to less than a monolayer of aluminum oxide. Thus, the Al ions terminate the TiO2 surface rather than form a distinct aluminum oxide layer. The aluminum ion surface treatment affects the solar cell in different ways: the potential of the conduction band is shifted, the electron lifetime is increased, and the electron transport is slower when aluminum ions are present between interconnected TiO2 particles.